Transient N‐glycosylation abnormalities likely due to a de novo loss‐of‐function mutation in the delta subunit of coat protein I. Issue 7 (10th May 2019) - Reunert, Janine; Rust, Stephan; Grüneberg, Marianne; Seelhöfer, Anja; Kurz, Daniel; Ocker, Volker; Weber, Dorothea; Fingerhut, Ralph; Marquardt, Thorsten
Abstract: Accurate glycosylation of proteins is essential for their function and their intracellular transport. Numerous diseases have been described, where either glycosylation or intracellular transport of proteins is impaired. Coat protein I (COPI) is involved in anterograde and retrograde transport of proteins between endoplasmic reticulum and Golgi, where glycosylation takes place, but no association of defective COPI proteins and glycosylation defects has been described so far. We identified a patient whose phenotype at a first glance was reminiscent of PGM1 deficiency, a disease that also affects N ‐glycosylation of proteins. More detailed analyses revealed a different disease with a glycosylation deficiency that was only detectable during episodes of acute illness of the patient. Trio‐exome analysis revealed a de novo loss‐of‐function mutation in ARCN1, coding for the delta‐COP subunit of COPI. We hypothesize that the capacity of flow through Golgi is reduced by this defect and at high protein synthesis rates, this bottleneck also manifests as transient glycosylation deficiency.